1988
DOI: 10.1007/bf01872838
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic behavior of the human red cell Ca2+ pump revealed by disulfonic stilbenes

Abstract: A systematic study was made of the action of 4-acet-amido-4'-isothiocyanostilbene-2,2'-disulfonic acid (SITS) and 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid (DIDS) on active Ca2+ transport of human erythrocytes. Pumping activity was estimated in inside-out vesicles (IOV's) by means of Ca2+-selective electrodes or use of tracer 45Ca2+. The stilbenes exhibited an approximately equal inhibitory potency and their action could be overcome by carbonyl cyanide p-trifluoromethoxyphenylhydrazone (FCCP) at low but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…1 and 3 are both fit with a hyperbolic curve, i.e., a Hill coefficient of 1. The stoichiometry of PMCA has been reported to be 1 Ca 2ϩ -2 H ϩ and 1 Ca 2ϩ -1 H ϩ (11,19,21,25,26,31), and our activation curves are consistent with 1 H ϩ activating. However, although our data do not require a model with 2 H ϩ activating, our data also do not eliminate such a model.…”
Section: Histidine or Cysteine In Release Site?supporting
confidence: 86%
See 1 more Smart Citation
“…1 and 3 are both fit with a hyperbolic curve, i.e., a Hill coefficient of 1. The stoichiometry of PMCA has been reported to be 1 Ca 2ϩ -2 H ϩ and 1 Ca 2ϩ -1 H ϩ (11,19,21,25,26,31), and our activation curves are consistent with 1 H ϩ activating. However, although our data do not require a model with 2 H ϩ activating, our data also do not eliminate such a model.…”
Section: Histidine or Cysteine In Release Site?supporting
confidence: 86%
“…The Ca 2ϩ pump not only mediates Ca 2ϩ efflux, but also proton (H ϩ ) influx. The H ϩ influx in red blood cells was initially inferred from indirect experiments (6,21,25,26,31). We have used a pH stat technique to measure directly Ca 2ϩ /H ϩ exchange in intact red blood cells (19).…”
mentioning
confidence: 99%
“…The negatively charged amino-reactive reagent DIDS and its dihydro derivative H2DIDS have been widely used in the study of both anion exchange (Zaki et al, 1975;Lepke et al, 1976;Cabantchik et al, 1978;Kasai & Taguchi, 1981) and the relationship between anion fluxes and those of other ionic species, including Ca2+ (Campbell & MacLennan, 1980;Waisman et al, 1981Waisman et al, , 1982Romero & Ortiz, 1988). However, these compounds appear to operate in different systems in a way that is not directly related to anion translocation (Campbell & MacLennan, 1980;Niggli et al, 1982; Waisman et al, 1982;Kimura et al, 1988;Pedemonte & Kaplan, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…mZIP14 can transport zinc as well as iron (II) (Liuzzi, Aydemir, Nam, Knutson, & Cousins, 2006). However, the mechanism of inhibition by DIDS for other proteins, such as the Ca 2þ -ATPase, is not well understood (Romero & Ortiz, 1988;Waisman, Smallwood, Lafreniere, & Rasmussen, 1982). Interestingly, it was observed that labeling with 4,4 0 -diisothiocyanatostilbene-2,2 0 -disulfonic acid (DIDS), a lysine-reactive probe, reduced 109 Cd 2þ uptake in a concentration-dependent manner.…”
Section: The Cation Selectivity Of the Zip Transportersmentioning
confidence: 99%